2018
DOI: 10.1080/02699052.2018.1466197
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ attitudes and behaviours related to paediatric mild traumatic brain injury: results from the 2014 DocStyles survey

Abstract: Objective: Explore healthcare providers’ experiences managing mTBI and better understand their use of mTBI assessment tools and guidelines. Cross-sectional Methods: A random sample of 1,760 healthcare providers responded to the web-based DocStyles survey between June 18 and 30, 2014. The sample included family/general practitioners, internists, pediatricians, and nurse practitioners who reported seeing pediatric patients. We examined their experiences with mTBI to identify opportunities to increase preparedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition, the signs and symptoms of mTBI can be subtle and easily missed in acute care settings 14 . To add to that challenge, many acute care and emergency medicine providers report insufficient training to effectively diagnose and manage mTBI 20 . Thus, a reliable and objective mTBI diagnosis remains a critical unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the signs and symptoms of mTBI can be subtle and easily missed in acute care settings 14 . To add to that challenge, many acute care and emergency medicine providers report insufficient training to effectively diagnose and manage mTBI 20 . Thus, a reliable and objective mTBI diagnosis remains a critical unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatricians are often tasked with managing the care of patients who have suffered a concussion; however, in a recent survey, only 45% of health care providers felt "very prepared" about making decisions regarding when to return to learning or return to sports [43]. The Concussion in Sports Group [44] highlighted the importance of using objective neuropsychological assessment results in making return to school and return to play decisions.…”
Section: Role Of Neuropsychologistsmentioning
confidence: 99%
“…The Concussion in Sports Group [44] highlighted the importance of using objective neuropsychological assessment results in making return to school and return to play decisions. When making return to play and return to sport decisions, 24.6% of healthcare providers reported "seldom" using objective screening or assessment and 22% reported "never" using objective measures [43]. Furthermore, there is wide documentation of healthcare providers providing inadequate education to pediatric patients and their families related to managing concussive events [45,46].…”
Section: Role Of Neuropsychologistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, healthcare providers may need reliable tools to assess head injuries and concussions. In a recent national study of health care national providers who saw pediatric patients in their practice, over half (59%) reported that they diagnosed or managed pediatric patients with a mTBI (or concussion) within the last 12 months, however only 44.4% reported feeling very prepared to make decisions pertaining to the patients’ safe return to school and sports after the mTBI [11]. Some researchers assert that clinical decision support tools, such as computerized neuropsychological tests with baseline and post-concussion assessments, would be useful for healthcare providers to identify symptoms and make management decisions with sports-related concussion [1113].…”
Section: Introductionmentioning
confidence: 99%